1971
DOI: 10.1017/s0007087400011225
|View full text |Cite
|
Sign up to set email alerts
|

William H. Bragg's Corpuscular Theory of X-Rays and γ-Rays

Abstract: The modern corpuscular theory of radiation was born in 1905 when Einstein advanced his light quantum hypothesis; and the steps by which Einstein's hypothesis, after years of profound scepticism, was finally and fully vindicated by Arthur Compton's 1922 scattering experiments constitutes one of the most stimulating chapters in the history of recent physics. To begin to appreciate the complexity of this chapter, however, it is only necessary to emphasize an elementary but very significant point, namely, that whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…William Henry Bragg, in a response to the Bremsstrahlen theory, presented Sommerfeld with an alternative view which became known as the neutral-pair hypothesis (Stuewer, 1971;Wheaton, 1983, pp. 87-90).…”
Section: The Quest For the Nature Of X-raysmentioning
confidence: 99%
See 1 more Smart Citation
“…William Henry Bragg, in a response to the Bremsstrahlen theory, presented Sommerfeld with an alternative view which became known as the neutral-pair hypothesis (Stuewer, 1971;Wheaton, 1983, pp. 87-90).…”
Section: The Quest For the Nature Of X-raysmentioning
confidence: 99%
“…However, the Braggs soon became aware that the phenomenon is indeed a diffraction phenomenon of the primary X-rays. While W. H. Bragg hoped for an explanation that would finally account both for the wave and particle aspect of X-ray phenomena (Stuewer, 1971;Wheaton, 1983, p. 208), his son began to adopt the idea of a wave interference -even though entirely different from Laue. On 11 November 1912, Bragg junior reported at Cambridge about the Munich experiment.…”
Section: A Discovery Based On Misapprehensionsmentioning
confidence: 99%
“…In 1906 Charles Glover Barkla had shown that X-rays could be polarized and this became key evidence that they were wave-like in nature. However due to Sir William Henry Bragg's work on radioactivity at the University of Adelaide, the very same evidence that was seen to support the wave theory of light could also be interpreted by a corpuscular description of X-rays (Stuewer 1971). It would take intuition from Max von Laue to add indisputable evidence for the wave-like nature of X-rays.…”
Section: X-rays: Wave or Particle?mentioning
confidence: 96%
“…At this point however, it was not clear whether X-rays were even related to visible light (Stuewer 1971) let alone whether they were waves or particles (Holton et al 2014). In 1906 Charles Glover Barkla had shown that X-rays could be polarized and this became key evidence that they were wave-like in nature.…”
Section: X-rays: Wave or Particle?mentioning
confidence: 99%
“…However, there were serious doubts about whether X-rays are waves. William Henry Bragg, in a response to the Bremsstrahlen theory, presented Sommerfeld with an alternative view which became known as the neutral-pair hypothesis (Stuewer, 1971;Wheaton, 1983, pp. 87-90).…”
Section: The Quest For the Nature Of X-raysmentioning
confidence: 99%